Effect of processing on nutritive value of corn cobs: Chemical composition and in vitro digestibility - Yulistiani, Dwi; Puastuti, W; Wina, E; ., Supriati (Indonesian Journal of Animal and Veterinary Sciences, 2012)
One of the causes of in low productivity of ruminants in Indonesia is the lack of continual availability of high quality feed. Agriculture by-product such as corn cob is potential to be used as roughage for ruminants. However its nutrient quality is low; therefore, processing needs to be done to increase its nutrient quality.Â  The objective of the study was to obtain technology which able to increase the nutritive value of corn corb. Corn cobs were ground to obtain corn grain size and then treated with one of six treatments. These treatments were (1). Urea treatment at the level 3% of DM corn cob, (2). Fermentation using Trichoderma viridae; (3). Combination of fermentation using T. viridae and urea at the level 0.5% DM, (4). Fermentation using Aspergilus niger, (5). Fermentation using A. niger and urea at the level of 0.5% DM and (6). Ensiling of corn cob. All treated samples were dried in an oven then were ground for chemical analyses and in vitro digestibility. The study was done using randomised completely design and the data was analyzed using SAS programe v6.1. Result shows that untreated corn cob had low quality nutritive value which was indicated by its low protein content (2.9%) and low in vitro digestibility (42.5%). All treatments could increase corn cobâs protein contents; the highest increase was on urea treatment and fermentation of corn cob using A. niger supplemented with urea (210 and 172% respectively). The in vitro digestibility was only significantly increased by urea treatment where its digestibility was increased by 43%. On the other hand, fermentation using A. niger either with or without urea supplementation increased neutral detergent fibre digestibility by 300% and 200%. In conclusion, nutritive value of a corn cob can be improved by urea treatment at the level of 3% or by fermentation using A. niger. Key Words: Corn Cob, Silage, Ammoniation, Fermentation